Model-Model Pembelajaran Berbasis Konstruktivisme dalam Upaya Meningkatkan Kemandirian Siswa pada Pembelajaran Pendidikan Agama Islam - Naila Karima; Indah Muliati; Rini Rahman (An-Nuha, 2026)
Islamic Religious Education (IRE) plays a strategic role in shaping students’ moral and spiritual character. However, its learning process is still dominated by conventional approaches, focusing on memorization and lectures, resulting in passive student engagement. This study aims to examine the constructivist learning model as a relevant alternative to improve IRE learning quality. Using a qualitative descriptive approach through literature review, data were collected from scientific articles published between 2020 and 2025. The findings reveal that the constructivist model encourages active, critical, and contextual religious understanding through strategies such as cooperative learning and reflective dialogue. It promotes meaningful learning experiences, enhances student participation, and fosters internalization of Islamic values. Nevertheless, challenges remain in teacher readiness and learning infrastructure. The study concludes that constructivist-based models are essential for realizing transformative IRE that shapes both intellectual and spiritual competencies.